2018
DOI: 10.1503/cmaj.180543
|View full text |Cite
|
Sign up to set email alerts
|

Containing health myths in the age of viral misinformation

Abstract: It has never been easier in human history to find and share information about health and medicine. But much of the information found on the Internet and shared on social media is inaccurate and potentially dangerous. As more people seek health content online, it will become increasingly important for medical researchers and practitioners to find effective ways of steering the public toward evidence-based content and away from myths and pseudoscience.Viral misinformation has become a threat to public health. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 4 publications
1
22
0
4
Order By: Relevance
“…Social media provides connectedness for those that hold similar beliefs and further encourages misconceptions about health. 11 Furthermore, ample research suggests that there is a significant amount of misinformation related to health matters on social media that can lead to potentially dangerous health practices.…”
Section: Discussionmentioning
confidence: 99%
“…Social media provides connectedness for those that hold similar beliefs and further encourages misconceptions about health. 11 Furthermore, ample research suggests that there is a significant amount of misinformation related to health matters on social media that can lead to potentially dangerous health practices.…”
Section: Discussionmentioning
confidence: 99%
“…Translating scientific evidence to practice involves a number of challenges. To begin with, we are currently living in a time of plentiful, but often inaccurate, information (2). As a result, a growing number of consumers access health and nutrition information from internet sources (3,4) and this may be flawed.…”
Section: Introductionmentioning
confidence: 99%
“…Since the mid-2000s, the evidence demonstrating that the content people access online can affect significantly their health behaviors [ 70 ] has been growing. Researchers have connected proanorexia content with the rise in eating disorder incidence [ 71 ], antivaccination messages with a loss of trust in public vaccination programs [ 72 ], celebrity endorsements with mass uptake of fad diets and increased reliance on homeopathy and naturopathy over clinical intervention [ 9 ], and participation in specific chatrooms with suicidal ideation [ 73 ]. Furthermore, research has also shown that the creation of this potentially harmful content is not always unintentional.…”
Section: Prevention Protection and Promotion: An Action Ontologymentioning
confidence: 99%
“…As a consequence of the lack of intervention in this state of affairs, hesitancy around getting vaccinated is now a major global health concern. At the same time, myriad online communities promoting self-harm, anorexia, and homeopathy now exist; unevidenced and unregulated apps are freely available for download; and the reckless promotion of fad diets and unproven wellness trends by celebrities on unregulated social media platforms is leading to the spread of various dangerous behaviors [ 9 , 10 ]. In short, as [ 11 ] states, “A child who needlessly experiences disabilities caused by measles, an adult who dies after stopping a statin despite having high-risk coronary heart disease, and a patient with cancer who ceases chemotherapy in favour of a bogus alternative are all victims of misinformation that is being promulgated on social media and other internet platforms.”…”
Section: Introductionmentioning
confidence: 99%